VOLCANIC DEGASSING OF BROMINE AND IODINE: EXPERIMENTAL FLUID/MELT PARTITIONING DATA AND APPLICATIONS TO STRATOSPHERIC CHEMISTRY - Bureau H.; Keppler H.; Metrich N. (My University, 2000)
In order to understand the degassing behavior of heavy halogens in volcanic processes, we experimentally studied the distribution of Cl, Br, and I between albite melt and hydrous fluids containing 0.01-2 wt% of NaCl, NaBr, or NaI, respectively. All experiments were carried out at 2 kbar and 900°C in rapid-quench cold-seal autoclaves with a run duration of 7 days. The major element compositions and Cl contents of the glassy run products were measured by electron microprobe. Bromine and iodine were measured by proton-induced X-ray emission. Fluid compositions were obtained by mass balance. All halogens investigated were found to partition strongly into the fluid phase. Over the range of concentrations studied, the halogen contents in the melt are proportional to the concentrations in the fluid. The fluid/melt partition coefficients, Df/m, are 8.1+/-0.2 for Cl, 17.5+/-0.6 for Br, and 104+/-7 for I. The logarithm of Df/m is linearly correlated with the ionic radius of the halogenide ion. On the basis of our experimental data, we estimate the amount of bromine injected into the stratosphere by major volcanic explosions. For the 1991 Mount Pinatubo eruption, we obtain Br yields of 11-25 kt as minimum estimates. These numbers are comparable to the total annual influx of bromine into the stratosphere from all other natural and anthropogenic sources (about 100 kt/year). Since bromine is much more efficient in destroying stratospheric ozone than chlorine, it could at least be partially responsible for the massive ozone depletion observed after the 1991 Mount Pinatubo eruption.
Keywords: CHLORINE; BROMINE; IODINE; HALOGENS; PARTITIONING; DEGASSING; VOLCANISM; STRATOSPHERE; OZONE